1986
DOI: 10.1159/000124665
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Estradiol-Positive Feedback Action on LH Release during Prepubertal Period in Rats Treated Postnatally with an Opiate Antagonist

Abstract: The purpose of this study was to determine the role of endogenous opioid peptides in the differentiation of the neuroendocrine brain that leads to estradiol-dependent LH release in female but not in male rats. Newborn intact or gonadectomized rats were given an opiate antagonist, naltrexone, with or without an opiate agonist, morphine, or saline alone during the critical period of the sexual differentiation of the brain (days 1–10). These animals were weaned on day 21 and injected with estradiol benzoate (EB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Thus the endogenously evoked oestradiolpositive feedback on LH release seemed to be effectively present in both naltrexone-treated and in saline-treated 31-day-old rats. Lira et al (1986) reported the absence of this oestradiol-positive feedback on day 24 in neonatally naltrexone-treated Sprague-Dawley rats. Although the central mechanism for oestradiol-positive feedback might have been restored or developed between days 24 and 31 in our rats, it seems likely that the difference in rat strain may also play a role.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus the endogenously evoked oestradiolpositive feedback on LH release seemed to be effectively present in both naltrexone-treated and in saline-treated 31-day-old rats. Lira et al (1986) reported the absence of this oestradiol-positive feedback on day 24 in neonatally naltrexone-treated Sprague-Dawley rats. Although the central mechanism for oestradiol-positive feedback might have been restored or developed between days 24 and 31 in our rats, it seems likely that the difference in rat strain may also play a role.…”
Section: Discussionmentioning
confidence: 97%
“…A clear advancement of the onset of puberty in the female rat after neonatal administration of naloxone was reported by Sirinathsinghji, Motta & Martini (1985), whereas Lira, Phipps & Sarkar (1986) reported impairment of the development of the oestradiolpositive feedback action on LH release during prepuberty after neonatal administration of another opioid antagonist, naltrexone. The results of Lira et al (1986) suggest that naltrexone has a delaying effect on the onset of puberty in the female.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Control of sexual differentiation Lira et al 1986, Romano et al 1990) and induces feminization in males (Sandberg et al 1990, Johnston et al 1992. Reznikov et al (2005) have also suggested that endogenous opiates are the mediators of the feminizing effect induced by stress.…”
Section: Opiatesmentioning
confidence: 99%